ANALISIS KONTRASTIF SISTEM MORFEMIS NOMINA BAHASA JAWA-INDONESIA - Kasno Atmo Sukarto (Sawo Manila, 2010)
The similarity between Javanese and Indonesian appears to both characteristics; these languages are agglutinative and there are many mono morpheme words. For that reason, we have to conduct a contrastive analysis. A contrastive analysis is really challenging and highly hesitancy. On the contrary, the most different thing in mono morpheme process is the grouping system of vocals which in Indonesian there is no such thing. Besides, there is a contrary in the process of increasing or decreasing sounds.